Postać jako wehikuł adaptacji: musical „Kapitan Żbik i żółty saturator” - Woźniak, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
The article presents an analysis of the adaptation idea for the musical Kapitan Żbik i żółty saturator (Captain Żbik and the yellow carbonator) directed by Wojciech Kościelniak. The direct inspiration for the show created in 2020 in the Syrena theatre in Warsaw was the comic book series published between 1968 and 1982. The interpretation of the cultural significance of the colourful books forms the introduction to the analysis of the show. The author also presents how the literary genre of the source affects the screenplay and the characters. The stage and costume design, the spoken texts and songs and the acting style all refer back to the comic books. The article is an attempt at determining how similar the staged Captain Żbik is to its source and what adaptation tools have been used to adjust the comic book language to the requirement of a theatre stage.